2002
DOI: 10.1080/1071576021000006716
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenic Actions of Thermally-stressed Culinary Oils in Rats

Abstract: Lipid oxidation products (LOPs), generated in culinary oils during episodes of thermal stressing can give rise to cellular damage. The aims of this study were to determine whether orally-administered, LOP-containing thermally-stressed safflower oil exerts teratogenic actions in rats, and whether this effect could be prevented by co-administration of alpha-tocopherol (alpha-TOH). Safflower oil was heated for a period of 20 min according to standard frying practices and stored at -20 degrees C under N2. Four exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…It is attractive to speculate that increased LDL oxidation and the lipid peroxides generated during this process may play a role in the congenital malformations associated with GDM and obesity. In the experimental animal model, the oral administration of lipid peroxides generated from heated culinary oils increases the rate of congenital malformations [36]. Further studies need to be made to show the possible relationship between increased LDL susceptibility to oxidation and the higher incidence of congenital anomalies observed in GDM pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…It is attractive to speculate that increased LDL oxidation and the lipid peroxides generated during this process may play a role in the congenital malformations associated with GDM and obesity. In the experimental animal model, the oral administration of lipid peroxides generated from heated culinary oils increases the rate of congenital malformations [36]. Further studies need to be made to show the possible relationship between increased LDL susceptibility to oxidation and the higher incidence of congenital anomalies observed in GDM pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the absorption of these toxic compounds from the diet has been proved and confirmed in experiments with animals (Tinsley et al, 1981;Kanazawa et al, 1985;Kanazawa and Ashida, 1985;Grootveld et al, 1998;Kim et al, 1999;Jenkinson et al, 1999;Indart et al, 2002).…”
Section: Introductionmentioning
confidence: 87%
“…The obtained results are given in Table 1, and it can be observed that the content of 4-hydroxy-trans-2-nonenal was of the same order in the oil before and after frying and also in the oil retained by the potatoes, the high concentration reached being noteworthy (near 60 mg of 4-hydroxy-trans-2-nonenal per Kg of oil). Due to the fact that this compound can be absorbed from the diet (Kanazawa et al, 1985;Grootveld et al, 1998;Indart et al, 2002) the potential high content in oils rich in linoleic acyl groups submitted to repeated frying episodes should be considered as a subject of health concern.…”
Section: Determination and Ocurrence Of Oαβuas In Foodsmentioning
confidence: 99%
“…In this paper, it has been shown that these toxic compounds can also be produced in foods rich in linoleic acyl groups submitted to the thermal oxidative conditions used in this study. This fact is very important because some authors have pointed out that these oxygenated aldehydes are readily absorbed from the diet [39][40][41], which has been confirmed in experiments with animals [42][43][44].…”
Section: Compoundsmentioning
confidence: 99%